1998
DOI: 10.1111/j.2042-7174.1998.tb00920.x
|View full text |Cite
|
Sign up to set email alerts
|

Reducing Adverse Prescribing Discrepancies Following Hospital Discharge

Abstract: General medical patients from an east London teaching hospital were recruited into intervention and comparison groups. Those recruited into the intervention group were given a copy of a letter listing their drugs prescribed at discharge and asked to give it to their regular community pharmacist when they went to obtain their prescribed drugs following hospital discharge. A comparison group returned home without a letter for their community pharmacist. Recruited patients were visited in their own homes once the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
68
1

Year Published

2002
2002
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(71 citation statements)
references
References 3 publications
2
68
1
Order By: Relevance
“…Other studies comparing pharmacist-acquired medication histories with those obtained by physicians reported similar results, with an unintentional discrepancy being reported for around 60% of medicines (13,16). The percentage of medicines presented with a discrepancy was lower (approx.…”
Section: Resultssupporting
confidence: 69%
“…Other studies comparing pharmacist-acquired medication histories with those obtained by physicians reported similar results, with an unintentional discrepancy being reported for around 60% of medicines (13,16). The percentage of medicines presented with a discrepancy was lower (approx.…”
Section: Resultssupporting
confidence: 69%
“…In a review of 22 studies the authors concluded that medication history errors are common at the time of hospital admission [17]. Different interventions have had some effect on the number of medication errors or emergency department visits [18,19]. We welcome studies that compare different interventions or combinations of interventions in this field.…”
Section: Discussionmentioning
confidence: 96%
“…The process involves comparing the Studies from the UK, Holland, Canada and the U.S. have been based on development of models for medication reconciliation at hospital discharge. This includes telephone follow-up by a pharmacist [12], and discharge summaries to pharmacies [13,14,[25][26][27][28][29] and to the general practitioner [27,28,30]. To our knowledge, our discharge summary is the first systematic tool enabling information to be produced for the patient and to the next level of care by the responsible person, the physician.…”
Section: Discussionmentioning
confidence: 99%
“…A review article reports that of the medication errors identified, 11-59% were thought to be of clinical importance [3]. Various types of medication errors are frequent in hospitals [4,5] and in the interface between care levels [6][7][8][9][10][11][12][13][14][15][16]. Insufficient quality in the transfer of information on a patient's medications has recently been highlighted as one of the most important problems in health care, and international and national programs have been developed for information and help [16].…”
Section: Introductionmentioning
confidence: 99%